Multiple receptors involved in human rhinovirus attachment to live cells - Rankl, Christian (National Academy of Sciences, 2008)
Minor group human rhinoviruses (HRVs) attach to members of the low-density lipoprotein receptor family and are internalized via receptor-mediated endocytosis. The attachment of HRV2 to the cell surface, the first step in infection, was characterized at the single-molecule level by atomic force spectroscopy. Sequential binding of multiple receptors was evident from recordings of characteristic quantized force spectra, which suggests that multiple receptors bound to the virus in a timely manner. Unbinding forces required to detach the virus from the cell membrane increased within a time frame of several hundred milliseconds. The number of receptors involved in virus binding was determined, and estimates for on-rate, off-rate, and equilibrium binding constant of the interaction between HRV2 and plasma membrane-anchored receptors were obtained.